Task Force report: European Respiratory Society statement for defining respiratory exacerbations in children and adolescents with bronchiectasis for clinical trials - KARADAĞ, BÜLENT TANER (My University, 2022)
Copyright © The authors 2022.Bronchiectasis is being diagnosed increasingly in children and adolescents. Recurrent respiratory exacerbations are common in children and adolescents with this chronic pulmonary disorder. Respiratory exacerbations are associated with an impaired quality-of-life, poorer long-term clinical outcomes and substantial costs to the family and health systems. The European Respiratory Society (ERS) clinical practice guideline for the management of children and adolescents with bronchiectasis provided a definition of acute respiratory exacerbations for clinical use but to date there is no comparable universal definition for clinical research. Given the importance of exacerbations in the field, this ERS task force sought to obtain robust definitions of respiratory exacerbations for clinical research. The panel was a multidisciplinary team of specialists in paediatric and adult respiratory medicine, infectious disease, physiotherapy, primary care, nursing, radiology, methodology, patient advocacy and parents of children and adolescents with bronchiectasis. We used a standardised process that included a systematic literature review, parents\" survey and a Delphi involving 299 physicians (54 countries) caring for children and adolescents with bronchiectasis. Consensus was obtained for all four statements drafted by the panel as the disagreement rate was very low (range 3.6% to 6.4%). The panel unanimously endorsed the four consensus definitions for: non-severe and severe exacerbations as an outcome measure; non-severe exacerbation for studies initiating treatment and; resolution of a non-severe exacerbation; for clinical trials involving children and adolescents with bronchiectasis. This ERS task force proposes using these internationally derived, consensus-based definitions of respiratory exacerbations for future clinical paediatric bronchiectasis research.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SOLUNUM SİSTEMİ; Clinical Medicine (MED); CLINICAL MEDICINE; RESPIRATORY SYSTEM; Akciğer ve Solunum Tıbbı; Pulmonary and Respiratory Medicine